Phosphorylation regulates spontaneous and evoked transmitter release at a giant terminal in the rat auditory brainstem - Oleskevich, Sharon (Blackwell Science Inc, 2000)
1. The role of phosphorylation in synaptic transmission was investigated at a large glutamatergic terminal, the endbulb of Held, on bushy cells in the rat anteroventral cochlear nucleus (AVCN). 2. Whole-cell recordings of excitatory postsynaptic currents (EPSCs) were used to examine the effects of kinase inhibitors and activators on low-frequency (baseline) evoked release, spontaneous release, paired-pulse facilitation (PPF) or depression (PPD), repetitive stimuli and recovery from depression. 3. Application of the kinase inhibitor H7 (100 μm) reduced low-frequency evoked EPSC amplitude (by 15 %) and simultaneously increased PPF (or reduced PPD), with no significant change in other aspects of transmission. H7 did not affect the amplitude or frequency of spontaneous miniature EPSCs. 4. Phorbol esters increased EPSC amplitude (by 50 %) with a concomitant decrease in PPF (or increase in PPD), and reduced the final EPSC amplitude during repetitive stimuli. The effect of phorbol esters was due exclusively to protein kinase C (PKC) activation, as the specific PKC inhibitor bis-indolylmaleimide (Bis) completely blocked the potentiating effect of phorbol esters on EPSC amplitude. 5. Significantly, phorbol esters did not increase the evoked EPSC amplitude at connections in which release was maximized using high extracellular calcium concentrations (4–6 mm). 6. Phorbol esters increased the frequency of spontaneous miniature EPSCs in physiological calcium (by 275 %), and in high extracellular calcium (by 210 %) when phorbol esters did not increase the evoked EPSC amplitude. 7. Our results are most consistent with the actions of H7 to decrease low-frequency release probability and phorbol esters to increase low-frequency release probability at the endbulb-bushy cell synaptic connection in the AVCN. The effects of H7 and phorbol esters on paired-pulse responses and tetanic depression appear to be largely consequential to these changes in low-frequency release probability.